2011
DOI: 10.1111/j.1746-1561.2011.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the School Environment in School Violence Prevention Efforts*

Abstract: Background-Numerous studies have demonstrated an association between characteristics of the school environment and the likelihood of school violence. However, little is known about the relative importance of various characteristics of the school environment or their differential impact on multiple violence outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Creating a culture of health in school depends on integrating other interlocking systems to include the family and community. Increasing dialogue between school personnel and parents to talk about issues of race and racism cultivates a culture of respect and trust . A vital aspect of such change efforts includes sharing evidence on school suspension to guide discussions on reducing bias and improving decision‐making.…”
Section: Implications For School Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating a culture of health in school depends on integrating other interlocking systems to include the family and community. Increasing dialogue between school personnel and parents to talk about issues of race and racism cultivates a culture of respect and trust . A vital aspect of such change efforts includes sharing evidence on school suspension to guide discussions on reducing bias and improving decision‐making.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…Increasing dialogue between school personnel and parents to talk about issues of race and racism cultivates a culture of respect and trust. [59][60][61] A vital aspect of such change efforts includes sharing evidence on school suspension to guide discussions on reducing bias and improving decisionmaking. Integrating families and other community partners in implementing school improvement plans have several benefits.…”
Section: Increase Collaborative and Restorative Practicesmentioning
confidence: 99%
“…When violence occurs at school it can lead to victims feeling depressed and isolated. Researchers have indicated that some students who are victims of school violence skip school occasionally due to not feeling safe (Johnson, Burke, & Gielen, 2011). Furthermore, Blosnich and Bossarte (2011) indicated that even low-level violence can result in negative emotional and psychological consequences for the victims.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parental and community involvement can also help to decrease fears that students may have in regards to school violence (Hong & Eamon, 2012) Another step that some schools have taken to reduce violence and create a safer environment came through the use of metal detectors. Critics argue that schools should be hesitant in acquiring metal detectors because they can negatively impact the school environment and increased security can actually escalate violence (Johnson et al, 2011). Since there has been no real data to support the use of metal detectors in schools (Fritz & Radka, 2010;Hankin, Hertz, & Simon, 2011), others believe that instruction on violence prevention may be more beneficial and more cost effective than metal detectors (Hankin et al, 2011).…”
Section: Armed Employees and School Policy 14mentioning
confidence: 99%
“…Another purpose of SROs is to create an intermediary for the schools and law enforcement . This intermediary serves to benefit both the school and the police department: the school benefits in this relationship since the school environment is directly impacted by the community environment (Johnson, Burke, & Gielen, 2011); law enforcement benefits from this relationship because schools are often manifestations of larger community issues . In studying averted school shootings, some characteristics that those schools had in common were: a strong connection between the schools and local law enforcement; interventions occurred at the family, neighborhood, and school levels; and communication along with relationships were key in preventing a tragedy (Daniels et al, 2007;Daniels et al, 2010).…”
Section: Armed Employees and School Policy 14mentioning
confidence: 99%